A glass marble ball in the maxillary sinus, transorbital floor penetration: A case report - Jirawarakul, Krissanaporn (Chulalongkorn Medical Journal, 2023)
Foreign bodies in the sinus are uncommon and transorbital foreign bodies in the maxillary sinus are very rare. We hereby described a case of a glass marble ball about 1.6 cm in diameter that penetrated into the right maxillary sinus through the orbital floor without globe rupture. The foreign body in the sinus should be removed to prevent further infection and other complications. In this case, the glass marble ball was removed by a transnasal endoscopic technique with a widened maxillary antrum after guarding of orbital ball upward in order to prevent the orbital injury. There were no immediate and long term postoperative complications.